SURVEY ON THE PERCEPTION OF MEDICAL ERROR REPORTING AND PATIENT SAFETY CULTURE AMONG NURSES AND MIDWIVES AT LE VAN THINH HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: The study aims to survey the perception of medical error reporting and patient safety culture among nurses and midwives at Le Van Thinh Hospital in 2025.Methodology: This was a descriptive cross-sectional study conducted from March to August 2025 at Le Van Thinh Hospital, Ho Chi Minh City. The study subjects included 209 nurses and midwives with a minimum of 12 months of service. Data was collected using a self-administered questionnaire, which included the Hospital Survey on Patient Safety Culture (HSOPSC) tool.Results:Reporting Perception: The average perception score for medical error reporting was low (1,92 ± 0,88/5). Staff were more willing to report less severe situations (e.g., "situations with the risk of causing a medical error" was 2,35±0,94) and had the lowest perception score for serious errors. Work unit/Block was a statistically significant related factor to perception (p < 0.001).Patient Safety Culture: The overall positive response rate reached 62.5%, which is lower than the internationally recommended standard. Strong areas included "Teamwork within units" (97.1%) and "Organizational learning – Continuous improvement" (93.3%). Areas reaching only a low level were "Teamwork across units" (35.4%) and "Hospital management support for patient safety" (41.0%).Conclusion: The perception of medical error reporting among nurses and midwives at Le Van Thinh Hospital in 2025 was low. Patient safety culture is emerging but needs further reinforcement at the leadership and inter-unit levels.
Keywords: Medical error, Medical error reporting, Patient Safety, Patient Safety Culture, Nurse, Midwife, Le Van Thinh Hospital.